N-Methyl-D-Aspartate (NMDA)-Type Glutamate Receptors and Demyelinating Disorders: A Neuroimmune Perspective - Abhari, Amir P.; Etemadifar, Masoud; Yazdanpanah, Niloufar; Rezaei, Nima (Mini Reviews in Medicinal Chemistry, 2022)
N-methyl-D-aspartate receptors (NMDARs) are ionotropic glutamate receptors, highly important in regulating substantial physiologic processes in the brain and the nervous system, and disturbance in their function could contribute to different pathologies. Overstimulation and hyperactivity of NMDARs, termed glutamate toxicity, could promote cell death and apoptosis. Meanwhile, their blockade could lead to dysfunction of the brain and nervous system. A growing body of evidence has demonstrated the prominent role of NMDARs in demyelinating disorders and anti- NMDAR encephalitis. Herein, we provide an overview of NMDARs’ dysfunction in the physiopathology of demyelinating disorders such as multiple sclerosis and neuromyelitis optica spectrum disorders.
Keywords: glutamate receptors